Use of an In‐line Digestive Cartridge With Enteral Nutrition Improves the Weight Trajectory of 2 Children With Cystic Fibrosis Complicated by Another Medical Diagnosis. (16th April 2018) - Giguere‐Rich, Catherine; Mathew, Amy; Reid, Elizabeth; Autore, Kimberly; Guill, Margaret F.
Abstract: This clinical observation describes the enteral nutrition (EN) management of 2 toddlers at high nutrition risk due to cystic fibrosis (CF), exocrine pancreatic insufficiency, and comorbid medical conditions. The first case report describes a boy with severe malabsorption after intestinal resection. The second case report reviews a boy with CF and neuroblastoma. When pancreatic enzyme replacement therapy with EN was not effective or appropriate, use of an in‐line digestive cartridge was initiated. While using the digestive cartridge, both children showed improvements in their anthropometric measures. This observation reviews the nutrition management throughout their clinical course and describes the use of a digestive cartridge with EN.